2016
DOI: 10.3390/ijms17040471
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Profile of Complement Components in Podocytes

Abstract: Podocytes are critical for maintaining the glomerular filtration barrier and are injured in many renal diseases, especially proteinuric kidney diseases. Recently, reports suggested that podocytes are among the renal cells that synthesize complement components that mediate glomerular diseases. Nevertheless, the profile and extent of complement component expression in podocytes remain unclear. This study examined the expression profile of complement in podocytes under physiological conditions and in abnormal pod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
3
30
1
Order By: Relevance
“…Staining with Periodic Schiff Acid showed massive sclerosis and glomerular damage ( Figure 7A). In these studies, we confirmed the results of Li et al (35), concerning the glomerular upregulation of C3 mRNA in PAN ( Figure 7B). In addition, we detected an increased induction of CFH in comparison to H 2 O-treated controls (Figure 7C).…”
Section: Glomerular C3 and Cfh Is Upregulated In Pansupporting
confidence: 92%
See 2 more Smart Citations
“…Staining with Periodic Schiff Acid showed massive sclerosis and glomerular damage ( Figure 7A). In these studies, we confirmed the results of Li et al (35), concerning the glomerular upregulation of C3 mRNA in PAN ( Figure 7B). In addition, we detected an increased induction of CFH in comparison to H 2 O-treated controls (Figure 7C).…”
Section: Glomerular C3 and Cfh Is Upregulated In Pansupporting
confidence: 92%
“…After the detection of C3 production in podocytes, we were interested in investigating the possibility that podocytes secrete other components of the complement cascade. In keeping with the results from Li et al (35), we were also able to detect other components of the complement system in cultured podocytes (Supplementary Figure 1). Nevertheless, we were not able to detect mRNA for the later complement components C6, C7, C8, or C9.…”
Section: Cultured Podocytes Can Contribute To Local Complement Activasupporting
confidence: 91%
See 1 more Smart Citation
“…The association between PAH and SLE suggested that inflammatory process activate a proliferative and inflammatory pulmonary lesions, which eventually lead to vascular remodeling 20 , 27 . Activation of the complement system can directly contribute to vascular leakage, which was observed to be underlying PAH pathogenesis 12 , 28 . Our proteome data illustrated that plasma kallikrein (complement and coagulation cascades Pathway), complement component C9 and ranoclass II (both in systemic lupus erythematosus pathway), CD63 antigen, legumain, Cathepsin S, Cathepsin Z, lysosomal acid lipase(proteins in lysosome pathway) were highly enhanced in PAH, Whereas Histone H3.3, Histone H 3.1(proteins in systemic lupus erythematosus pathway), HMGB1 (base excision repair pathway) were considerably down-regulated in PAH progression, these proteins were markedly recovered by osthole treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Data that showed that increased C3 and C3a staining was also observed in the liver and spleen reflected a systemic complement activation (Supplemental Figure 1; supplemental material available online with this article; https://doi.org/10.1172/ jci.insight.131849DS1). The expression of C3aR, which is known to be present on different renal cells, including podocytes (26)(27)(28)(29), was then evaluated. Immunofluorescence analysis in the renal tissue of control mice revealed weak glomerular C3aR protein expression ( Figure 1C) that increased markedly in BTBR ob/ob mice, specifically in podocytes, as revealed by quantification of costaining of C3aR and nestin ( Figure 1C).…”
Section: Complement Activation and Consequent C3a Generation Occur Inmentioning
confidence: 99%